Effect of antibiotic treatment on sputum elastase in bronchiectatic outpatients in a stable clinical state. - Stockley, R A (1984)
Broad spectrum antibiotic treatment was given on 21 occasions to 15 patients with bronchiectasis who regularly produced purulent, elastase positive secretions. Although the results showed that sputum clearing--that is, changing from purulent to mucoid--largely depended on the pathogenic organism isolated, this was not exclusively the case and in some cases sputum growing sensitive organisms failed to clear whereas clearing occurred in other samples containing resistant organisms or no obvious pathogens. Clearing of sputum was achieved eventually in 12 of the patients and this was associated with the disappearance of elastase activity, although it returned in 10 patients within one week of stopping treatment. There was no change in sputum elastase where the sputum failed to clear. The clearance of elastase activity was associated with a decrease in protein transudation into the lung secretions. The sputum:serum albumin concentration ratio fell (p less than 0.005) from a mean (SD) of 2.32 (1.56) X 10(-2) in these 12 patients before treatment to 1.09 (0.40) X 10(-2) within the first week of treatment, but rose again to 2.07 (1.29) X 10(-2) within one week of stopping treatment. The results suggest that antibiotic treatment when patients are in a stable state may have a beneficial effect on the pathogenic nature of lung secretions and inflammation within the lung.